2019
DOI: 10.4081/oncol.2019.376
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer, human immunodeficiency virus and highly active antiretroviral treatment; implications for a high-rate seropositive region

Abstract: Sub-Saharan Africa is the region in the world with the most people infected with the human immunodeficiency virus (HIV). The incidence of breast cancer is also rising in the region. This transcript focusses on the burden of these two diseases when they converge in the same populace. This comprehensive literature review of the topic suggests a trend towards an increasing incidence of breast cancer in the HIV-infected population, and the rationale for such a tendency is hypothesized, especially in the context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 94 publications
1
4
1
Order By: Relevance
“…This study found an enigma concerning the association between breast cancer and retroviral infections. In contrast to published bodies of literature reporting lower or equivalent breast cancer rate in patients with retroviral infection compared to general population, our study found that the proportion of breast cancer patients with retroviral infection exceeded 10%, which is far more than the rate of retroviral infections in the capital, 3.4% [ 17 , 18 ]. We understand that the study was not designed to answer this question.…”
Section: Discussioncontrasting
confidence: 99%
“…This study found an enigma concerning the association between breast cancer and retroviral infections. In contrast to published bodies of literature reporting lower or equivalent breast cancer rate in patients with retroviral infection compared to general population, our study found that the proportion of breast cancer patients with retroviral infection exceeded 10%, which is far more than the rate of retroviral infections in the capital, 3.4% [ 17 , 18 ]. We understand that the study was not designed to answer this question.…”
Section: Discussioncontrasting
confidence: 99%
“…Breast: The literature reveals that breast carcinoma does not seem to increase in incidence within the HIV infected population. [30,31] In present study, all three patients presented with disseminated disease. Patients over a Period of 16 Years Attending a Tertiary Care Hospital Colorectal Cancer (CRC): O'Neill TJ et al reviewed colo rectal data of 1660 cases and concluded that risk of CRC is similar in people living with and without HIV.…”
Section: Discussionsupporting
confidence: 48%
“…reside in the 403 km 3 area of the capital, Lilongwe, located in the central region which primarily consists of Chewa (71%), Tumbuka (3.2%), and Lomwe (3.1%) tribes [11]. Though breast cancer represents approximately 4-7% of new female cancer diagnoses in Malawi, this incidence is predicted to increase due to population aging, 'Westernization' of lifestyles, declining morbidity and mortality related to infectious diseases such as HIV, and corresponding rise of non-communicable diseases [8,10,[12][13][14][15]. Given high HIV prevalence in SSA, HIV is a relatively common comorbidity among women with breast cancer in the region [16].…”
Section: Introductionmentioning
confidence: 99%